Study of ∑N interaction from the ∑p scattering experiment at J-PARC. (December 2020) - Miwa, K.; Ahn, J.K.; Akazawa, Y.; Aramaki, T.; Ashikaga, S.; Callier, S.; Chiga, N.; Choi, S. W.; Ekawa, H.; Evtoukhovitch, P.; Fujioka, N.; Fujita, M.; et al.
Abstract: A high statistics ∑ p scattering experiment has been performed at the K1.8 beamline in the J-PARC Hadron Experimental Facility. Data for momentum-tagged ∑ − beam running in a liquid hydrogen target were accumulated by detecting the π − p → K + ∑ − reaction with a high intensity π − beam of 20 M/spill. The number of the Σ − beam was about 1.7 × 10 7 in total. The ∑ − ρ elastic scattering and the ∑ − p → Λn inelastic scattering events were successfully observed with about 100 times larger statistics than that in past experiments.